Effects of speed extension on PCCI combustion and emissions in a heavy-duty diesel engine at medium load. (1st April 2022) - Lu, Yingying; Fan, Chao; Liu, Yize; Pei, Yiqiang
Highlights: Intake boost helps form lean mixture, increases the indicated thermal efficiency. Increasing speed retards ignition time and decreases over-rich mixture mass fraction. Increasing speed decreases NOx, soot, CO and UHC emissions simultaneously. Increasing speed increases the indicated thermal efficiency. Retarding injection timing decreases soot, CO and UHC emissions. Abstract: Effects of boost pressure, engine speed and multi-pulse injection timing on premixed charge compression ignition (PCCI) combustion and emissions in a heavy-duty diesel engine at medium load were studied experimentally and numerically. Results show that, intake boost makes the high temperature ignition timing advance, but the mass fraction of lean mixture increases dramatically and the mass fractions of rich and over-rich mixtures decrease significantly, indicating that intake boost helps the formation of lean and homogeneous mixture; the indicated thermal efficiency increases and the combustion loss decreases. When the engine speed is increased with other variables constant, the high temperature ignition timing is retarded, the mass fraction of over-rich mixture decreases; the NOx, soot, CO and UHC emissions are all decreased; the indicated thermal efficiency increases, the combustion loss decreases, but the exhaust loss increases. The delay of multi-pulse fuel injection timing with other variables constant shortens the mixing time, increases the mass fraction of over-rich mixture, and increases the initial soot generation. However, due to the combined effect of mixing space and combustion temperature, the final soot, CO and UHC emissions are all decreased, and the NOx emissions have little change; the indicated thermal efficiency increases, the combustion loss decreases, but the exhaust loss increases.